Reconfirmation of the presence of the non-native channel catfish in the Yahagi River, Aichi Prefecture - Tsuruta, Hirotsugu; Yoshida, Makoto A.; Yamamoto, Daisuke (Izunuma-Uchinuma Wetland Researches, 2024)
Recently, the distribution of channel catfish, Ictalurus punctatus, an invasive alien species, has been expanding in several water systems in Japan. The species’ first occurrence in the Yahagi River was confirmed in 2005. Since then, a local institute and citizen groups had been worked together to eliminate the species for 10 years. They caught over 100 individuals at Azuri and Koshido dams (Toyota City, Aichi Prefecture, approximately 53 km and 46 km upstream from the river mouth, respectively) in the middle reaches. The number of individuals captured peaked in 2010 and declined in 2011–2014. However, no surveys of the species have been conducted in the river since 2015; therefore, its current status is unknown. In this study, longline surveys were conducted to confirm the species’ presence at Azuri and Koshido dams using the same sampling method as in the past. Four surveys were conducted, once each at both dams in June 2021, once at Azuri dam in October and once at Koshido dam in November. A total of eight channel catfish were captured; three at Azuri dam (total length: 28.0–33.7 cm) and five at Koshido dam (total length: 53.5–73.0 cm). The age of the individuals estimated from body length was 2–6 years for three individuals captured at Azuri dam (i.e., they were born after 2015) and was 6+ years for five individuals captured at Koshido dam (i.e., they were born before 2015). The number of fish caught per hook (i.e., catch per unit effort, or CPUE) was 0.050 at Azuri dam and 0.073 at Koshido dam; the former was the second highest value following 2010 and the latter was the highest ever recorded. These results suggest that the population has recovered in the waters around both dams since 2014, possibly due to the reproduction of individuals that have survived at the time; the current population densities are estimated to be similar to or higher than those during the early 2010’s.